2020
DOI: 10.1038/s41419-020-2233-6
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible gastroenteritis virus targets Paneth cells to inhibit the self-renewal and differentiation of Lgr5 intestinal stem cells via Notch signaling

Abstract: Infection with transmissible gastroenteritis virus (TGEV) has been associated with villous atrophy within 48 h, which seriously disrupts intestinal homeostasis. However, the underlying mechanisms remain elusive. In this study, we found that TGEV infection severely disrupted intestinal homeostasis via inhibition of self-renewal and differentiation in Lgr5 intestinal stem cells (ISCs). Profoundly, TGEV-encoded NSP10/NSP16 protein complex-mediated the inactivation of Notch signaling provided a mechanistic explana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…We used immuno uorescence to demonstrate that hypoxia in uenced the expression of LGR5. Moreover, the levels of LGR5 have also been found to be in uenced by PI3K/Akt/mTOR [35], Wnt/β-catenin [36], and Notch signaling [37], suggesting that HIF-1α and hypoxia could also be involved in the regulation of LGR5. In a xenograft murine model of tumorigenesis using A549 NSCLC cells transfected with Tie1-shRNA, we found that the levels of stem cell markers, LGR5 and Ki67, were reduced and that tumors were more sensitive to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…We used immuno uorescence to demonstrate that hypoxia in uenced the expression of LGR5. Moreover, the levels of LGR5 have also been found to be in uenced by PI3K/Akt/mTOR [35], Wnt/β-catenin [36], and Notch signaling [37], suggesting that HIF-1α and hypoxia could also be involved in the regulation of LGR5. In a xenograft murine model of tumorigenesis using A549 NSCLC cells transfected with Tie1-shRNA, we found that the levels of stem cell markers, LGR5 and Ki67, were reduced and that tumors were more sensitive to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…We used immuno uorescence to demonstrate that hypoxia in uenced the expression of LGR5. Moreover, the levels of LGR5 are also in uenced by PI3K/Akt/mTOR [35], Wnt/ β-catenin [36], and Notch signaling [37], suggesting that HIF-1α and hypoxia could also be involved in the regulation of LGR5. In a xenograft murine model of tumorigenesis using A549 NSCLC cells transfected with Tie1-shRNA, we found that the levels of stem cell markers, LGR5 and Ki67, were reduced and that tumors were more sensitive to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…We used immuno uorescence to demonstrate that hypoxia in uenced the expression of LGR5. Moreover, the levels of LGR5 are also in uenced by PI3K/Akt/mTOR [35], Wnt/ β-catenin [36], and Notch signaling [37], suggesting that HIF-1α and hypoxia could also be involved in the regulation of LGR5. In a xenograft murine model of tumorigenesis using A549 NSCLC cells transfected with Tie1-shRNA, we found that the levels of Ki67 were reduced and that tumors were more sensitive to cisplatin.…”
Section: Discussionmentioning
confidence: 99%